Geography of tourist flows in the Russian Federation: statistics, trends, challenges - Anna Yur'yevna Aleksandrova (Наука. Инновации. Технологии, 2022)
The article discusses the geographical structure of Russian tourism market. The analysis covers 20-year period from the mid-1990s to 2015. The study summarizes large amount of statistical data from various official sources that allows following quantitative and qualitative changes in the geography of tourist flows in the Russian Federation. Current trends in international and domestic tourism development in Russia, such as the reduction in foreign holidays of tourists from Russia, reorientation of consumer demand for domestic trips and the growth of inbound tourist flow to the country, are highlighted. The reasons for structural changes in the geography of tourist lows are revealed. They include the drop in oil prices, sharp luctuations of the ruble exchange rate against foreign currencies, difficult economic situation in the country and its solvent demand reduction, the ban on the tours to the most popular outbound tourist areas - Egypt and Turkey, establishing of international sanctions against Russia, etc. The paper concludes that current economic crisis has led to a "tectonic shift" in Russian tourism industry and to a change in its paradigm. Prospects for its future prosperity are connected with domestic and inbound tourism development. However, outbound tourism is also important for any civilized society. All the three types of tourism form the entity which requires harmonious development for stability.